nsmedira
nsmedira

Reputation: 78

How can if/elif/else be replaced with min() and max()?

Working on an exercise from MIT's OpenCourseWare 6.01SC. Problem 3.1.5:

Define a function clip(lo, x, hi) that returns lo if x is less than lo, returns hi if x is greater than hi, and returns x otherwise. You can assume that lo < hi. ...don't use if, but use min and max.

Reformulated in English, if x is the least of the arguments, return lo; if x is the greatest of the arguments, return hi; otherwise, return x. Thus:

def clip(lo, x, hi):
    if min(lo, x, hi) == x:
        return lo
    elif max(lo, x, hi) == x:
        return hi
    else:
        return x

Maybe I am not understanding the problem correctly, but I can't figure out how to return a result without using if at all. How can the function be modified to remove the if/elif/else statements?

Link to original problem 3.1.5

Link to previous problem 3.1.4 (for context)

EDIT:

Comments/answers to this question helped me realize that my original plain English reformulation wasn't a great way to think about the problem. A better way to think about it would have been to determine which of the arguments is between the other two.

Upvotes: 0

Views: 1061

Answers (3)

Ateeq ur Rehman
Ateeq ur Rehman

Reputation: 1

Here you go, a value checking function without using if-else at all. While block will only run for once so there is no redundancy.

def clip(lo, x, hi):
    low = (min(lo, x) == x)
    high = (max(x, hi) == x)
    while low:
        return lo
    while high:
        return hi
    return x
    

EDIT: I don't know why he downvoted my code

Upvotes: -1

Paul Cornelius
Paul Cornelius

Reputation: 10946

One line of code:

#! python3.8

def clip(lo, x, hi):
    return max(min(x, hi), lo)

print(clip(1, 2, 3))
print(clip(2, 1, 3))
print(clip(1, 3, 2))

# Output
# 2
# 2
# 2

Upvotes: 2

Djaouad
Djaouad

Reputation: 22776

You can return this formula:

x + lo + hi - max(x, lo, hi) - min(x, lo, hi)

Arguing by cases:

Case 1:

If min(lo, x, hi) = lo and max(lo, x, hi) = hi
  x + lo + hi - max(x, lo, hi) - min(x, lo, hi) ==> x + lo + hi - hi - lo ==> x

Case 2:

If min(lo, x, hi) = lo and max(lo, x, hi) = x
  x + lo + hi - max(x, lo, hi) - min(x, lo, hi) ==> x + lo + hi - x - lo ==> hi

Case 3:

If min(lo, x, hi) = x and max(lo, x, hi) = hi
  x + lo + hi - max(x, lo, hi) - min(x, lo, hi) ==> x + lo + hi - hi - x ==> lo

The formula returns the expected answer on all possible cases.

Upvotes: 0

Related Questions